Rotation Control, Interlocking, and Self‐Positioning of Active Cogwheels. (10th September 2022) - Martinet, Quentin; Aubret, Antoine; Palacci, Jeremie
Abstract : Gears and cogwheels are elemental components of machines. They restrain degrees of freedom and channel power into a specified motion. Building and powering small‐scale cogwheels are key steps toward feasible micro and nanomachinery. Assembly, energy injection, and control are, however, a challenge at the microscale. In contrast with passive gears, whose function is to transmit torques from one to another, interlocking and untethered active gears have the potential to unveil dynamics and functions untapped by externally driven mechanisms. Here, it is shown the assembly and control of a family of self‐spinning cogwheels with varying teeth numbers and study the interlocking of multiple cogwheels. The teeth are formed by colloidal microswimmers that power the structure. The cogwheels are autonomous and active, showing persistent rotation. Leveraging the angular momentum of optical vortices, we control the direction of rotation of the cogwheels. The pairs of interlocking and active cogwheels that roll over each other in a random walk and have curvature‐dependent mobility are studied. This behavior is leveraged to self‐position parts and program microbots, demonstrating the ability to pick up, direct, and release a load. The work constitutes a step toward autonomous machinery with external control as well as (re)programmable microbots and matter. Abstract : We assemble autonomous cogwheels powered by active colloids forming the teeth. The control of the direction of rotation using the angular momentum of optical vortices is demonstrated. The dynamics of interlocking cogwheels in contact that roll over each other and can self‐position is studied. The work shows the potential of active colloids to form autonomous machinery with external control.